Growth variables and obstetrical risk factors in newborns are associated with psychomotor development at preschool ageAJOG Global Reports at a Glance - Arne Jensen, MD; Gerhard Neuhäuser, MD (Elsevier, 2023)
BACKGROUND: Low birthweight resulting from preterm birth or fetal growth restriction is associated with poor neurocognitive development and child psychopathology affecting school performance and educational success. Prediction of developmental performance may therefore serve as a basis for early intervention strategies to improve educational success and mental health of our children in a timely manner. OBJECTIVE: This study aimed to explore the predictive capacity of morphometric variables taken at birth and that of obstetrical risk factors to predict developmental performance at 4.3 (standard deviation, 0.8) years preschool age. We examined predicted Total psychomotor development score, predicted Developmental disability index, calculated Morphometric vitality index, and predicted Intelligence quotient, Maze test, and Neurologic examination optimality score in a large prospective screening (cranial ultrasound screening, n=5,301) and validation cohort (n=508,926). STUDY DESIGN: In a single-center cohort observational study design (data collection done from 1984-1988, analysis done in 2022), a prospective cranial ultrasound screening study (1984-1988) was carried out on 5,301 live-born infants, including 571 (10.8%) preterm infants (≤36 weeks gestation), on the day of discharge of the mother at 5 to 8 days postpartum from a level 3 perinatal center. Predicted psychomotor development as assessed by predicted Total psychomotor development score, predicted Developmental disability index, calculated Morphometric vitality index, and predicted Intelligence quotient, Maze test, and Neurologic examination optimality score, was calculated. We related growth variables and obstetrical risk factors to Psychomotor development indices, and calculated Morphometric vitality index using odds ratios, receiver operating characteristics, analysis of variance, and multivariate analysis of variance. RESULTS: The key result of our study is the observation that simple morphometric measures from newborns at birth like weight/head circumference ratio predict overall psychomotor development at 4.3 years (standard deviation, 0.8) of preschool age. Psychomotor development was assessed by predicted Total psychomotor development score, predicted Intelligence quotient, Maze test, and Neurologic examination optimality score, and related to weight/head circumference ratio in linear regression (P<.001) and ROC curve analyses (P<.001). Further, white matter damage strongly predicted adverse outcome in predicted Developmental disability index (P<.001). There was also a close correlation between calculated Morphometric vitality index and predicted Developmental disability index (P<.001). Finally, brain body weight ratio, weight/head circumference ratio, preterm birth, reduced Apgar at 10 minutes, weight/length ratio, and white matter damage yielded highest odds ratios for adverse outcome in predicted Total psychomotor development score and in predicted Developmental disability index (P<.001) and high effect sizes in reduced predicted Intelligence quotient, Maze test, and Neurologic examination optimality scores. CONCLUSION: Simple morphometric data, birth variables, and obstetrical risk factors bear predictive capacity for neurocognitive performance in children at 4.3 years (standard deviation, 0.8) of age and hence provide a basis for parental consultation and early intervention to improve school performance, educational success, and mental health in developed and developing countries.